PENGARUH PARTISIPASI MASYARAKAT, SISTEM PENGENDALIAN INTERNAL DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA - M Agus Sudrajat; Ali Tiyas Nugroho; Muhammad Cholis; Rihan Mustafa Zahri (ITB AAS Indonesia Surakarta, 2022)
The purpose of this study was to determine and analyze the influence of community participation, internal control systems and the use of information technology on village fund management accountability with professionalism as a moderating variable (a case study in villages in Ngawi district). The population in this study were village officials in 5 sub-districts receiving the largest allocation of village funds in Ngawi Regency amounted to 568 people and the sample was 104. The method in determining the sample used in this study was purposive sampling, while the data processing method used was multiple regression analysis. and MRA test. This study uses a survey method using primary data obtained from questionnaires distributed to respondents. The results of this study indicate that the community participation variable affects the accountability of village fund management, the internal control system and the use of technology do not affect the accountability of village fund management. The moderating variable of professionalism is significant in moderating the effect of the use of information technology on village fund management accountability, but professionalism is not able to moderate the effect of community participation and internal control systems on village fund management accountability. Keywords : Community Participation, Internal Control System, Utilization of Information Technology, Village Fund Management Accountability